Dose Effect of Tumor Necrosis Factor-α on In Vitro Osteogenic Differentiation of Mesenchymal Stem Cells on Biodegradable Polymeric Microfiber Scaffolds - Mountziaris, Paschalia M. (2009)
This study presents a first step in the development of a bone tissue engineering strategy to trigger enhanced osteogenesis by modulating inflammation. This work focused on characterizing the effects of the concentration of a pro-inflammatory cytokine, tumor necrosis factor alpha (TNF-α), on osteogenic differentiation of mesenchymal stem cells (MSCs) grown in a 3D culture system. MSC osteogenic differentiation is typically achieved in vitro through a combination of osteogenic supplements that include the anti-inflammatory corticosteroid dexamethasone. Although simple, the use of dexamethasone is not clinically realistic, and also hampers in vitro studies of the role of inflammatory mediators in wound healing. In this study, MSCs were pre-treated with dexamethasone to induce osteogenic differentiation, and then cultured in biodegradable electrospun poly(ε-caprolactone) (PCL) scaffolds, which supported continued MSC osteogenic differentiation in the absence of dexamethasone. Continuous delivery of 0.1 ng/mL of recombinant rat TNF-α suppressed osteogenic differentiation of rat MSCs over 16 days, which was likely the result of residual dexamethasone antagonizing TNF-α signaling. Continuous delivery of a higher dose, 5 ng/mL TNF-α, stimulated osteogenic differentiation for a few days, and 50 ng/mL TNF-α resulted in significant mineralized matrix deposition over the course of the study. These findings suggest that the pro-inflammatory cytokine TNF-α stimulates osteogenic differentiation of MSCs, an effect that can be blocked by the presence of anti-inflammatory agents like dexamethasone, with significant implications on the interplay between inflammation and tissue regeneration.